2013
DOI: 10.1371/journal.pone.0079909
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-Wide Identification of Regulatory Elements and Reconstruction of Gene Regulatory Networks of the Green Alga Chlamydomonas reinhardtii under Carbon Deprivation

Abstract: The unicellular green alga Chlamydomonas reinhardtii is a long-established model organism for studies on photosynthesis and carbon metabolism-related physiology. Under conditions of air-level carbon dioxide concentration [CO2], a carbon concentrating mechanism (CCM) is induced to facilitate cellular carbon uptake. CCM increases the availability of carbon dioxide at the site of cellular carbon fixation. To improve our understanding of the transcriptional control of the CCM, we employed FAIRE-seq (formaldehyde-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 56 publications
1
12
0
1
Order By: Relevance
“…In agreement with previous work (Berger et al, 2014), which clearly demonstrated an activation of the NAB1 promoter by carbon dioxide depletion via reporter assays, a transcriptome study revealed changes in NAB1 transcript abundance dependent on carbon dioxide supply (Winck et al, 2013).…”
Section: Introductionsupporting
confidence: 92%
See 4 more Smart Citations
“…In agreement with previous work (Berger et al, 2014), which clearly demonstrated an activation of the NAB1 promoter by carbon dioxide depletion via reporter assays, a transcriptome study revealed changes in NAB1 transcript abundance dependent on carbon dioxide supply (Winck et al, 2013).…”
Section: Introductionsupporting
confidence: 92%
“…Six of these motifs are present in the NAB1 promoter (Supplementary Figure S2, Supplementary Table S2), but none of them is located within the 152 bp region upstream of the translation start site. Moreover, according to Winck and co-workers, NAB1 (UniProt KB ID 126810) was contained in a cluster of early responding genes and mRNA levels increased about 7-fold one hour after the onset of carbon dioxide deprivation (Winck et al, 2013). NAB1 accumulation in response to carbon dioxide limitation requires LCRF ( Figure 3C) and results in a decline of LHCBM6 protein levels after six hours ( Figure 4F).…”
Section: )mentioning
confidence: 85%
See 3 more Smart Citations